Plant–soil feedback effects on conspecific and heterospecific successors of annual and perennial Central European grassland plants are correlated - Wilschut, Rutger A.; Hume, Benjamin C. C.; Mamonova, Ekaterina; van Kleunen, Mark (Nature plants, 2023)
Plant–soil feedbacks (PSFs), soil-mediated plant effects on conspecific or heterospecific successors, are a major driver of vegetation development. It has been proposed that specialist plant antagonists drive differences in PSF responses between conspecific and heterospecific plants, whereas contributions of generalist plant antagonists to PSFs remain understudied. Here we examined PSFs among nine annual and nine perennial grassland species to test whether poorly defended annuals accumulate generalist-dominated plant antagonist communities, causing equally negative PSFs on conspecific and heterospecific annuals, whereas well-defended perennial species accumulate specialist-dominated antagonist communities, predominantly causing negative conspecific PSFs. Annuals exhibited more negative PSFs than perennials, corresponding to differences in root–tissue investments, but this was independent of conditioning plant group. Overall, conspecific and heterospecific PSFs did not differ. Instead, conspecific and heterospecific PSF responses in individual species’ soils were correlated. Soil fungal communities were generalist dominated but could not robustly explain PSF variation. Our study nevertheless suggests an important role for host generalists as drivers of PSFs. This study shows correlated growth responses of conspecific and heterospecific plants in soils previously occupied by other plants, suggesting key contributions of generalist soil biota to plant–soil feedback interactions between succeeding plants.